Botulinum toxin (Botox) A for reducing the appearance of facial wrinkles: a literature review of clinical use and pharmacological aspect - Satriyasa BK (Dove Medical Press, 2019)
Bagus Komang SatriyasaDepartment of Pharmacology, Faculty of Medicine, Udayana University, Bali, IndonesiaBackground: Botulinum toxin (Botox) consists of 7 types of neurotoxins; however, only toxins A and B are used clinically. Botox A is used for several disorders in the field of medicine, particularly in dermatology, for cosmetic purposes. It is produced by the bacterium Clostridium botulinum and can be used as a treatment to reduce the appearance of wrinkles in the upper areas of the face, elevate the eyebrows and treat problems such as hyperhidrosis, lichen simplex, pompholyx (dyshidrotic eczema) and acne vulgaris.Objectives: This article provides a literature review regarding the general issue of Botox as a treatment for reducing facial wrinkle.Discussion: Botox works by blocking the release of acetylcholine, resulting in paralysis of the local muscles, which usually occurs 24 hrs to two weeks following Botox injection. This effect will last three to six months. The optimal dose of cosmetic Botox in dermatology is 20 units. Botox is relatively safe and does not result in any adverse side effects. However, in certain circumstances, the effect of Botox will gradually resolve, resulting in reduced muscle paralysis over time.Conclusion: Botox is good and safe medicine to reduce the appearance of facial wrinkles.Keywords: Botox, botulinum toxin, drug, facial wrinkles